2012
DOI: 10.5402/2012/401761
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Wind and Solar Electricity Generation in Bangladesh

Abstract: Wind and solar energies are the alternative energy sources that can be used to supplement the conventional energy sources particularly in Bangladesh. In this work, the aim is to assess the current wind and solar energy potential in Bangladesh. The wind data for the five stations obtained from Local Government Engineering Department have been assessed, but only two of them seem to be eligible for energy production. Annual average, monthly average, and hourly average wind speeds and wind power densities were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Bangladesh is situated in a very suitable geographical position for the solar radiation. Everyday we get bright sunshine 4 to 10 hours and solar radiation in our country is 4 and 6.55KJ/m 2 [5] [6]. In that case solar power is very helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh is situated in a very suitable geographical position for the solar radiation. Everyday we get bright sunshine 4 to 10 hours and solar radiation in our country is 4 and 6.55KJ/m 2 [5] [6]. In that case solar power is very helpful.…”
Section: Introductionmentioning
confidence: 99%
“…A research study found that the daily sunlight hours range from 10 to 7 h in Bangladesh, and the authors further reduced this by 54 % (to 4.6 h) to consider the effects of rainfall, cloud, fog, and dust on the solar panels [17][18][19].…”
Section: Energy Resourcementioning
confidence: 99%
“…Although the initial installation cost of solar photovoltaic (PV) systems is quite high, the consistent price hike of fossil fuels and increased generation of greenhouse gases have influenced us to conduct a research on performance evaluation and feasibility of solar-powered boats in Bangladesh [19,21,22]. Usually, solar boats include auxiliary source of energy to meet unsatisfied power demand during cloudy and partially cloudy days.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, approximately half of the Bangladeshi population still lack access to the national grid. Potential employment of solar and wind sources to fill some of this gap are limited by seasonal dependency: solar irradiation peaking between March and May, and wind speeds peaking during June and August [27]. Furthermore, of the average annual rainfall of 1.35 trillion cubic metres that Bangladesh receives, 80% occurs during the Monsoon season between the months of June and October [18,28].…”
Section: Rain Energy As a Complement To Hybrid Systemsmentioning
confidence: 99%